PENGEMBANGAN MODUL AJAR DENGAN MEDIA DIGITAL MATERI BANGUN DATAR MENGGUNAKAN MODEL PBL UNTUK KELAS II SD - Ignatius William Krisna Putra; Ignatia Esti Sumarah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
21st-century skills are essential for teachers in integrating rapidly advancing technology into the teaching and learning process. Teachers are required to utilize media, especially digital media, in classroom activities. This study aims to develop a teaching module using digital media for plane figures material based on the PBL (Problem-Based Learning) model for Grade II elementary school and to evaluate the quality of the developed module. The research employed the R&D (Research and Development) model with the ADDIE framework. Four validators participated in the study: one lecturer, one Grade II teacher, one language expert, and one ICT expert. Data collection techniques included a needs analysis questionnaire. Data analysis utilized both qualitative and quantitative approaches. The findings of this study are as follows: (1) The teaching module using digital media for plane figures material was developed through the five stages of ADDIE: Analyze, Design, Development, Implementation, and Evaluation. (2) The validated teaching module achieved a score of 3.75, categorized as